A review on latest developments and future prospects of heterogeneous catalyst in biodiesel production from non-edible oils. (January 2017) - Mardhiah, H. Haziratul; Ong, Hwai Chyuan; Masjuki, H.H.; Lim, Steven; Lee, H.V.
Abstract: The research on biodiesel production via heterogeneous catalyzed approach is continuously studied by scientist in order to gain a sustainable process for industrial production and to improve its fuel quality. The green resource of biodiesel feedstock and catalyst is the major criteria to influence the biodiesel yield and sustainability of the process. For the state of the art biodiesel production technology, heterogeneous catalyst received great attention for simple and low cost manufacturing process. In terms of easy separation and high reusability. The most special characteristic of heterogeneous catalyst is its tuning properties that generate acidic-basicity, surface area and porosity that can highly advance the variety of the feedstock for esterification/transesterification process. Different traits of the heterogeneous catalysts (solid base, solid acid, acid-base and bio-catalyst) are studied in this review as each holds a specialty of features to the process. Thus, the study of heterogeneous catalyst should continue to be evaluated and taken into account if the catalyst are to be employed in the commercial sector as that remains the pivotal goal of these studies. In consideration to the debate of food vs. fuel as well as low cost production, non-edible feedstock was further discussed by using heterogeneous catalyzed system.